2005
DOI: 10.1096/fj.04-2368fje
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin decreases NOS2 expression via inhibition of NAD(P)H oxidase: implications for protection against endotoxic shock in rats

Abstract: We investigated a possible beneficial role for bilirubin, one of the products of heme degradation by the cytoprotective enzyme heme oxygenase-1 in counteracting Escherichia coli endotoxin-mediated toxicity. Homozygous jaundice Gunn rats, which display high plasma bilirubin levels due to deficiency of glucuronyl transferase activity, and Sprague-Dawley rats subjected to sustained exogenous bilirubin administration were more resistant to endotoxin (LPS)-induced hypotension and death compared with nonhyperbilirub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
178
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(190 citation statements)
references
References 47 publications
9
178
3
Order By: Relevance
“…These data suggested that the effect of phycocyanin may be mediated by that of phycocyanobilin. Although the antioxidant effects of bilirubin are due to its strong radical scavenging activity, several reports have shown that bilirubin directly inhibits NAD(P)H oxidase activity (19,20). Interestingly, we and other investigators have shown that nonphagocytic NAD(P)H oxidases may be the main sources of ROS in the vascular tissues of diabetic animals and patients (11,13,16,18).…”
Section: Discussionmentioning
confidence: 71%
“…These data suggested that the effect of phycocyanin may be mediated by that of phycocyanobilin. Although the antioxidant effects of bilirubin are due to its strong radical scavenging activity, several reports have shown that bilirubin directly inhibits NAD(P)H oxidase activity (19,20). Interestingly, we and other investigators have shown that nonphagocytic NAD(P)H oxidases may be the main sources of ROS in the vascular tissues of diabetic animals and patients (11,13,16,18).…”
Section: Discussionmentioning
confidence: 71%
“…While spirulina -once harvested as a food by the Aztecs, and still used by Africans living near Lake Chad -has been popular as a supplement in "health food" circles for several decades, its true health-protective merit has only recently been discovered: phycocyanobilin (PCB), the chromophore bound to spirulina's chief protein, phycocyanin, can function as a potent inhibitor of NADPH oxidase, the enzyme complex that is the chief source of pathological oxidant stress in a wide range of health disorders. 51,52 In this regard, it appears to mimic the physiological activity of free bilirubin; [53][54][55][56] PCB can be converted within cells to phycocyanorubin, which is nearly identical in structure to bilirubin. 57 Although the clinical utility of ample intakes of spirulina has so far received little research attention, in numerous rodent studies orally administered spirulina or phycocyanin has shown potent anti-inflammatory, cytoprotective, and anti-atherogenic activities; these effects are most likely attributable to down-regulation of NADPH oxidase activity.…”
Section: Spirulina Has Profound Antioxidant Potentialmentioning
confidence: 99%
“…It displays anti-inflammatory activity in animal models of endotoxemia, septicemia and ischemia reperfusion injury (Fondevila et al, 2004;Wang et al, 2004;Keshavan et al, 2005;Lanone et al, 2005;Nakao et al, 2005;Overhaus et al, 2006;Kadl et al, 2007). Some of the proposed mechanisms of bilirubin including its ability to down-regulate expression of adhesion molecules, inhibit infiltration of inflammatory cells and production of nitric oxide (NO), and to reduce production of various inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%